Quality of Life of Undergraduate Students during the Epidemic of Coronavirus Disease 2019 (COVID-19) - กิ่งสวัสดิ์ กุลธิดา; ดวงจินดา อิทธิพล (Journal of Health Science of Thailand, 2023)
The coronavirus disease 2019 (COVID-19) pandemic affects quality of life, especially the students’ health. This study aimed to assess the quality of life of students during the epidemic of COVID-19 in a tertiary school. This study was a cross-sectional study and conducted between March – April 2020 in Sirindhorn College of Public Health, Suphan Buri Province, Thailand. The cluster sampling technique was applied to recruit 198 undergraduates in the College. Data were collected by using a questionnaire which was prepared based on the “WHOQOL-BREF-THAI”; and the data were analysed by descriptive statistics and multiple logistic regression with 95% confidence interval (CI). It was found that most samples were female (85.86%); and the average age was 20.06 years old (SD=1.18). The quality of life was at moderate to high level (80.00%). The factors significantly associated with quality of the undergraduates during the COVID-19 pandemic included mental factor (OR=0.62, 95%CI: 0.43 – 0.81), social relationship (OR=0.28, 95%CI: 0.11 – 0.46), and environment (OR=0.57, 95%CI: 0.37 – 0.77). Thus, communication is an importance measure to protect, prevent and rehabilitate students during an emerging or re-emerging pandemic.